2010
DOI: 10.1096/fj.09-143503
|View full text |Cite
|
Sign up to set email alerts
|

CCL8/MCP‐2 is a target for mir‐146a in HIV‐1‐infected human microglial cells

Abstract: MicroRNA-mediated regulation of gene expression appears to be involved in a variety of cellular processes, including development, differentiation, proliferation, and apoptosis. Mir-146a is thought to be involved in the regulation of the innate immune response, and its expression is increased in tissues associated with chronic inflammation. Among the predicted gene targets for mir-146a, the chemokine CCL8/MCP-2 is a ligand for the CCR5 chemokine receptor and a potent inhibitor of CD4/CCR5-mediated HIV-1 entry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 54 publications
4
73
0
1
Order By: Relevance
“…[30][31][32][33] Abnormal expression of miRNAs appears to be a common feature of many human diseases, ranging from cardiovascular disorders to cancer [30][31][32][33] and most recently inflammatory diseases. 9,34,35 Here, we present evidence showing that overexpression of the GSK3β inhibitor-dependent miRNAs, miR-98 and let-7g*, can decrease leukocyte adhesion to and migration across the BBB, in both in vitro and in vivo models. Not all miRNAs had similar abilities to improve BBB function in an in vitro model.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…[30][31][32][33] Abnormal expression of miRNAs appears to be a common feature of many human diseases, ranging from cardiovascular disorders to cancer [30][31][32][33] and most recently inflammatory diseases. 9,34,35 Here, we present evidence showing that overexpression of the GSK3β inhibitor-dependent miRNAs, miR-98 and let-7g*, can decrease leukocyte adhesion to and migration across the BBB, in both in vitro and in vivo models. Not all miRNAs had similar abilities to improve BBB function in an in vitro model.…”
Section: Discussionmentioning
confidence: 82%
“…8 For instance, miR-155 and miR-146a regulate a variety of immune reactions, including production of cytokines by T and B cells and the germinal center B-cell response. 9 miRNA profiling suggests that miR-126 is expressed mainly in endothelial cells. 10 Additional endothelial miRNA clusters have been identified: miR-17-92, miR-23-27-24, and miR-222-221 (many miRNAs are encoded by polycistronic miRNA genes).…”
Section: Introductionmentioning
confidence: 99%
“…Upon lipopolysaccharide (LPS) stimulation and virus infection, miR-146a acts as a negative feedback regulator and restrains the Toll-like receptor signaling pathways by targeting IRAK1/2 and TRAF6 in various innate cells such as monocytes, lung epithelial alveolar cells, and microglial cells. [7][8][9][10] In the adoptive immune system, miR-146a has previously been reported to target Fas-Associated protein with Death Domain to modulate activation-induced cell death and interleukin-2 (IL-2) expression in Jurkat T cells. 11 Ablation of miR-146a in mice leads to increased numbers of Treg cells but impairs their suppressor function because of the unrestrained function of STAT1.…”
Section: Introductionmentioning
confidence: 99%
“…Increased IRF-3 can, in turn, further exacerbate neuroinflammation by promoting the expression of miR-155 [48], suggesting a mechanism by which Tat exposure may further amplify chronic inflammation that contributes to eventual neurological dysfunction in HAND. It has also been reported that infection of microglia by HIV leads to increased expression of miR-146a, which subsequently suppress proinflammatory behavior and the release of CCL8/monocyte chemoattractant protein 2 (MCP-2) [49]. As MCP-2 can serve to block cellular entry by HIV, the role of miR-146a may have duel effect in perpetuating HAND by both suppressing endogenous antiviral proteins and decreasing the release of MCP-2.…”
Section: Regulation Of Neuroinflammation By Non-coding Rnamentioning
confidence: 99%